Therapeutic effects of auriculotherapy on anxiety syndromes among adolescents: A scoping review protocol (Research, Society and Development, 2021)
Introduction: anxiety syndromes are amidst the most frequent among adolescents appearing to be in the first forms of psychopathology. Drug Therapy and psychotherapy are strongly used in anxiety treatment, however, other therapeutic strategies are also been used, such as auriculotherapy, which consists of activating reflex points in the ear in order to improve mental and physical health. Objectiv: to map available evidences about the therapeutics effects of auriculotherapy on anxiety syndromes among adolescents. Inclusion criteria: This review will consider studies that include adolescents (10 to 19 years old) diagnosed with anxiety of any nature defined by the Diagnostic and Statistical Manual of Mental Disorders (DSM V) and that have undergone auriculotherapy to treat these clinical conditions. Methods: A three-step search strategy will be used for this review.  The databases to be searched include MEDLINE (PubMed), CINAHL, LILACS, Scielo/ BDENF, Scopus, Embase and Web of Science. Quantitative and qualitative studies will be considered. Only studies published in English, Spanish and Portuguese will be included, with no date limit. The extracted data will be presented in a diagram or tabulated in a way that aligns with the objective of this scoping review. A narrative summary will also be presented.